Mary Shelley's Frankenstein and Self–expression of the Pregnant Mother's Fears (Journal of the College of Basic Education, 2022)
Frankenstein (1816) is an impressive novel known as a story ofterror, and many critics and movies present it to mean so. But, MaryShelley (1797 – 1851), in her preface in the revised edition of 1831,describes the novel as: "one which speaks to the mysterious fears of ournature". 1 [emphasis added]. That is,